Study of the Structure and Properties of ZnS Utilized in a Fluorescence Biosensor - Y. Ren; H. Zhou; X. Wang; Q. W. Liu; X. D. Hou; G. F. Zhang (Stem Cells International)
ZnS materials have been widely used in fluorescence biosensors to characterize different types of stem cells due to their excellent fluorescence effect. In this study, ZnS was prepared by vulcanizing nano-Zn particles synthesized using a DC arc plasma. The composition and structure of the ZnS materials were studied by X-ray diffraction (XRD), and their functional group information and optical properties were investigated by using IR spectrophotometry and UV-vis spectrophotometry. It has been found that the synthesized materials consist of Zn, cubic ZnS, and hexagonal ZnS according to the vulcanization parameters. Crystalline ZnS was gradually transformed from a cubic to a hexagonal structure, and the cycling properties first increase, then decrease with increasing sulfurization temperature. There is an optimal curing temperature giving the best cycling performance and specific capacity: the material sulfurized thereat mainly consists of cubic β-ZnS phase with a small quantity of Zn and hexagonal α-ZnS. The cubic phase ZnS has better conductivity than hexagonal ZnS, as evinced by electrochemical impedance spectroscopy (EIS). The ZnS (as prepared) shows board absorption, which can be used in fluorescence biosensors in cell imaging systems.